Chemical and cellular oxidant production induced by naphthalene secondary organic aerosol (SOA): effect of redox-active metals and photochemical aging. Issue 1 (December 2017) - Tuet, Wing; Chen, Yunle; Fok, Shierly; Gao, Dong; Weber, Rodney; Champion, Julie; Ng, Nga
Abstract Exposure to air pollution is a leading global health risk. Secondary organic aerosol (SOA) constitute a large portion of ambient particulate matter (PM). In this study, the water-soluble oxidative potential (OP) determined by dithiothreitol (DTT) consumption and intracellular reactive oxygen and nitrogen species (ROS/RNS) production was measured for SOA generated from the photooxidation of naphthalene in the presence of iron sulfate and ammonium sulfate seed particles. The measured intrinsic OP varied for aerosol formed using different initial naphthalene concentrations, however, no trends were observed between OP and bulk aerosol composition or seed type. For all experiments, aerosol generated in the presence of iron-containing seed induced higher ROS/RNS production compared to that formed in the presence of inorganic seed. This effect was primarily attributed to differences in aerosol carbon oxidation state $${\boldsymbol{(}}{\bar{{\bf{O}}{\bf{S}}}}_{{\bf{c}}}{\boldsymbol{)}}$$ ( O S ¯ c ) . In the presence of iron, radical concentrations are elevated via iron redox cycling, resulting in more oxidized species. An exponential trend was also observed between ROS/RNS and $${\boldsymbol{(}}{\bar{{\bf{O}}{\bf{S}}}}_{{\bf{c}}}{\boldsymbol{)}}$$ ( O S ¯ c ) for all naphthalene SOA, regardless of seed type or aerosol formation condition. This may have important implications as aerosol have an atmospheric lifetime of a week, over which $${\boldsymbol{(}}{\bar{{\bf{O}}{\bf{S}}}}_{{\bf{c}}}{\boldsymbol{)}}$$ ( O S ¯ c ) increases due to continued photochemical aging, potentially resulting in more toxic aerosol.